Valorisation of local almond genotypes regarding their biochemical and mineral compositions - Gouta H.; Khelifa R.; Laaribi I.; Mechri B.; Molino F.; Estopañán G.; Juan Esteban T. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
The new tendency for intensification of almond plantations has induced a clear neglect of local ecotypes and cultivars that have proved high performances and good adaptation to many biotic and abiotic stresses. Prospecting the main producing regions in Tunisia has demonstrated a high genetic diversity. In addition, all of the pomological, biochemical and mineral characterizations have confirmed the potentialities of some local genotypes in comparison to the newly introduced cultivars. The analysis of their content in some biochemical compounds such as antioxidant has furthermore shown that some landraces are highly rich in α, γ and δ-tocophérols. Our result reported that the mineral composition of this nut is dominated by phosphor, calcium, iron, sodium, zinc and copper. In comparison to some introduced cultivars such as ‘Mazzetto’, ‘Lauranne’ and ‘Supernova’ many local ecotypes presented high performances. In fact the ecotype ‘BF2’, was highly rich in potassium and phosphor while ‘TL7’ in calcium. Additionally, the dominance of ‘khoukhi’, ‘Dillou’ and ‘Blanco’ for the iron element composition is another statement in favour of existent possibilities for a better valorisation of the local germplasm and consequently for its better preservation.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)